A preliminary checklist of the praying mantids of Comoé National Park, Ivory Coast (Insecta: Mantodea) - Schwarz, Christian J.; Pohl, Marius; Frank, Erik T. (Zootaxa, 2023)
The Comoé National Park (CNP), located in the north-eastern part of the Ivory Coast, is strongly influenced by the river Comoé, which is eponymous for the park. Gallery forests along the river, forest islands, open grasslands, bush and tree savannas of various densities offer diverse habitats that harbor both forest and savannah praying mantis species. We present a preliminary checklist of praying mantids (Insecta: Mantodea) of the CNP. Specimens were collected in 2000 and 2017‒2019, resulting in 35 species in 13 families. Two species, Ischnomantis werneri (Giglio-Tos 1916) and Solygia sulcatifrons (Audinet-Serville 1838), were recorded for the first time in Ivory Coast. Additional 47 species, which are expected to occur in the CNP, are listed here.